Characterizing nanoscale changes in the activity of VEGFR-2 on glioma microvascular endothelial cell membranes using atomic force microscopy - Zhou, Dexiang; Zhan, Shengquan; Zhou, Dong; Wang, Peng; Chen, Guangzhong; Qin, Kun; Lin, Xiaofeng (Experimental and therapeutic medicine, 2017)
The aim of the current study was to demonstrate the distribution of VEGFR-2 on glioma microvascular endothelial cells on a nanoscale and investigate changes in VEGFR-2 activity following treatment with the VEGFR-2 inhibitor and agonist sorafenib and bradykinin, respectively. Three groups were evaluated in this study: Control glioma microvascular endothelial cells, sorafenib-treated glioma microvascular endothelial cells and bradykinin-treated glioma microvascular endothelial cells. Changes in the activity of VEGFR-2 on the glioma microvascular endothelial cell membranes following treatment with sorafenib and bradykinin were characterized by atomic force microscopy (AFM). Colloidal gold-labeled immune complexes and AFM were used to visualize the distribution of VEGFR-2 on the cell membranes. In the control group, VEGFR-2, which was observed as numerous globular structures, was evenly distributed on the cell surface membranes. The majority of the receptors were active. In the sorafenib group, only a few globular structures were observed on the cell membranes, with a density significantly lower than that in the control group (P<0.01). Furthermore, compared with the control group, fewer of the receptors were active. In the bradykinin group, numerous globular structures were densely distributed on the cell membranes, with a density significantly higher than that in the control group (P<0.01). The distribution and activity of VEGFR-2 on glioma microvascular endothelial cell membranes treated with sorafenib and bradykinin suggested that the activity of VEGFR-2 could be regulated by its inhibitor or agonist.